Text-based language learning in terms of trilingual education (Eurasian Journal of Philology Science and Education, 2020)
The article notes the importance of creating an educational environment that meets the new requirements, in which the emphasis is on language skills and the ability to apply this knowledge in a particular situation. At the same time, the skills of working with text are defined as fundamental and universal, as they are relevant within the framework of each school subject. The effectiveness of the formation of students’ communicative skills depends on how the text will adequately meet the goals. In this regard, an important task arises before the teacher, the significance of which lies in the proper organization of educational activities for working with educational text. At the same time, the textual component of the textbooks of the Russian, Kazakh and English languages is of great importance.Attention is paid to the development of pre-text and post-text tasks of the educational text, which develop students’ habit of systematically and purposefully working with textual information. In this regard, describes the techniques and methods of working with the text incorporated in the new textbooks on languages. The question is raised about the purposeful work of the teacher in shaping and improving the skills of independent or collective work with the text of an educational nature. It is noted that the work in this direction contributes to the proper planning and organization of language lessons on the updated content of education.As a result of the analysis of educational material, it is concluded that the system of text exercises aimed at the development of students’ speech activity should stimulate the skills and abilities to master oral and written forms of speech for further independent educational activities. It is noted that this is an important part of student-teacher-based textbook collaboration.